Qualitative aspects in the managing activities of nursing care - Ximena Ibarra Mendoza (Universidad de Alicante, 2012)
Current and future nursing demands a new focus to allow its adaptation to the scientific advances in order to deliver a humanized clinical practice. This process requires the association between academic activities of nursing and clinical practice, reframing the buildings of conceptual and theoretical outlines, whose lineaments must emphasize into the family and collectivity, where the relationship health - disease - context - human development and social involvement became fundamental pillars, given that the philosophical roots of this profession and its social character have sustained as fundamental principles aspects such as the reaffirmation of the integrity of the human being, and the process of care as something significant and humanitarian that contributes to the preservation of mankind, not only because of the human - human transactions, but also for the requirements of knowledge, moral, social and personal commitment of the nursing, in the context and in the space. Pondering of these matters is the main objective of the present article, exploring the concept of management of care under the perspective of the professional education and the clinical practice, followed by a brief analysis of the scientific evolution of the profession in time; then it includes concepts and definitions about professional identity and nursing care, concluding with the conceptualization of the management of the care, along with some proposals in order to achieve the quality in the nursing care, with compromise of work for the future development.